DEVELOPMENT OF ANTIACNE GEL FORMULATION AND MINIMUM INHIBITORY CONCENTRATION DETERMINATION FROM CARICA PAPAYA LEAVES EXTRACT (CARICA PAPAYA A LINN.) - Ardina , Yustine
Acne occurs when there is blockage at pilosebaceous and inflammation that is caused by Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. To cure acne, a dosageform which has good penetration, its maximum contact time, and suitable dosage is needed. Traditionally, Carica papaya leaves had been used as anti acne agent by applying solution of crushed Carica papaya leaves directly to skin. One of suitable dosageform was gel, which has high water content so it can hydrate the stratum corneum and minimize further inflammation as a result of oil accumulation on skin pores. Carica papaya extract contains papain (keratolytic, antimicrobial agent) and carpaine (antibacterial agent) which could act as an active compound of antiacne agent. This research aimed to optimize the Carica papaya extract gel formula as antiacne agent. In this research a stable and effective gel formulation to Staphylococcus epidermidis and Propionibacterium acnes had been made. Research methodology divided into four steps, which including extract and simplicia characterization, antibacterial activity determination, optimization and evaluation of all the formulas. Simplicia is extracted by maceration using ethanolwater (1:3). Then, the extract and simplicia characterization was carried out by phytochemical screening, determination of water, determination of extractable matter, thin layer chromatography, extracts specificgravity determination, pH value determination, and determination of microorganism (total viable aerobic count). The minimum inhibition concentration (MIC) of the extract determined after it diluted into several concentration, then compared to pure papain and standard tetracycline. The extract and papain that have inhibitory zone diameter equivalent to tetracycline 3% w/v against Staphylococcus epidermidis and Propionibacterium acnes were then developed to become a gel formula. The orientation of gelbase composition was made with three gelbase, such as Carbopol 934, hydroxypropyl methyl celuloce (HPMC), dan hydroxypropyl cellulose low viscosity (HPCLV) with several concentration. Based on the result of gelbase composition orientation, organoleptic evaluation, pH evaluation, and viscosity evaluation, the best gelbase HPMC and HPCLV had been chosen. Antiacne gel formula from Carica papaya extract and papain were then evaluated for their activity using the MIC test. The result was compared to the result that comes from MIC test for Carica papaya extract and formula evaluation included organoleptic evaluation, homogenity, microorganism growth, sineresis, pH, and viscosity had done. Based on the result, Carica papaya extract gel was effective against 8,65.10 (9)cfu/mL of Staphylococcus epidermidis, but was ineffective against 2,7.10 (7) cfu/mL of Propionibacterium acnes. This means that Carica papaya extract gel could be used to avoid further acne inflammation, such as secondary inflammation by Staphylococcus epidermidis. Inhibition zone diameter for Carica papaya extract gel with HPCLV base was 19,80 0,30 mm, while the Inhibition zone diameter for HPMC base was 15,27 0,25 mm. Based on the result of pH and viscosity evaluation, Carica papaya extract gel with 30 % w/v HPC-LV base was physically more stable than those with 5 % w/v HPMC base. Carica papaya extract gel with HPC-LV base was more effective and more stable than the gel with HPMC base.